The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1186/1476-511x-9-96
|View full text |Cite
|
Sign up to set email alerts
|

Association between CETP Taq1B and LIPC -514C/T polymorphisms with the serum lipid levels in a group of Tehran's population: a cross sectional study

Abstract: BackgroundLow level of high density lipoprotein cholesterol (HDL-C) has high prevalence in the Tehran Lipid and Glucose Study (TLGS) cohort. About 50% of the inter-individual variation in serum HDL-C levels is genetically determined. Polymorphisms in cholesteryl ester transfer protein (CETP) and hepatic lipase (LIPC) genes have been found to be associated with the metabolism and serum concentration of the HDL-C.ObjectivesTo determine the association between Taq1B polymorphism in CETP gene and -514C/T polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 43 publications
(52 reference statements)
3
17
0
Order By: Relevance
“…34 Because HL catalyzes the hydrolysis of TG from intermediate-density lipoprotein and LDL, 35 such defects in the HL gene due to the promoter variant -480 C/T may lead to hypertriglyceridemia. Studies on an interactive effect between HL (also known as LIPC [lipase, hepatic]) gene variants and apolipoprotein E2 and that included C-514T,G-250A variants showed strong association of the TT genotype of the -514 C/T variant with hypertriglyceridemia among healthy Canadian adults 36 and similar association with serum triglycerides among an Iranian population, 37 strengthening the finding among NGT subjects in the present study. Although a few studies have shown quite a significant association with HDL-C in other ethnic populations, 38-40 the present study did not find any association with HDL-C.…”
Section: Discussionsupporting
confidence: 85%
“…34 Because HL catalyzes the hydrolysis of TG from intermediate-density lipoprotein and LDL, 35 such defects in the HL gene due to the promoter variant -480 C/T may lead to hypertriglyceridemia. Studies on an interactive effect between HL (also known as LIPC [lipase, hepatic]) gene variants and apolipoprotein E2 and that included C-514T,G-250A variants showed strong association of the TT genotype of the -514 C/T variant with hypertriglyceridemia among healthy Canadian adults 36 and similar association with serum triglycerides among an Iranian population, 37 strengthening the finding among NGT subjects in the present study. Although a few studies have shown quite a significant association with HDL-C in other ethnic populations, 38-40 the present study did not find any association with HDL-C.…”
Section: Discussionsupporting
confidence: 85%
“…This trend of association was consistent in all ethnic groups and genders although statistical significance was attained only in the Chinese men. Significant association of the B2 allele with elevated HDL-C was also reported for the Framingham population [11], Chinese population [23], Iranian population [19,20] and Tunisian population [9]. In their studies, the protective effects of the B2 allele on the development of CAD were observed in association with increased HDL-C and decreased CETP activity.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, a meta-analysis, based on the data from year 1970 to 2008, also found that individuals with TaqIB B2 allele had higher mean HDL-C concentrations and lower mean CETP activity compared with carriers of B1 allele [13]. Besides, the relationship between TaqIB polymorphism and HDL-C levels was also confirmed by other studies [18,19]. But the association between CETP TaqIB and CAD risk lacks consistency.…”
Section: Discussionmentioning
confidence: 87%